Plasma levels of aminothiols, nitrite, nitrate, and malondialdehyde in myelodysplastic syndromes in the context of clinical outcomes and as a consequence of iron overload - Pimková, Kristýna; Chrastinová, Leona; Suttnar, Jiří; Štikarová, Jana; Kotlín, Roman; Čermák, Jaroslav; Dyr, Jan Evangelista (Oxidative medicine and cellular longevity, 2014)
The role of oxidative stress in the initiation and progression of myelodysplastic syndromes (MDS) as a consequence of iron overload remains unclear. In this study we have simultaneously quantified plasma low-molecular-weight aminothiols, malondialdehyde, nitrite, and nitrate and have studied their correlation with serum iron/ferritin levels, patient treatment (chelation therapy), and clinical outcomes. We found significantly elevated plasma levels of total, oxidized, and reduced forms of cysteine (P < 0.001), homocysteine (P < 0.001), and cysteinylglycine (P < 0.006) and significantly depressed levels of total and oxidized forms of glutathione (P < 0.03) and nitrite (P < 0.001) in MDS patients compared to healthy donors. Moreover, total (P < 0.032) and oxidized cysteinylglycine (P = 0.029) and nitrite (P = 0.021) differed significantly between the analyzed MDS subgroups with different clinical classifications. Malondialdehyde levels in plasma correlated moderately with both serum ferritin levels (r = 0.78, P = 0.001) and serum free iron levels (r = 0.60, P = 0.001) and were significantly higher in patients with iron overload. The other analyzed compounds lacked correlation with iron overload (represented by serum iron/ferritin levels). For the first time our results have revealed significant differences in the concentrations of plasma aminothiols in MDS patients, when compared to healthy donors. We found no correlation of these parameters with iron overload and suggest the role of oxidative stress in the development of MDS disease.
Keywords: Ferritins; Nitrates; Iron Overload; oxidační stres; železo; výsledek terapie; dusitany; Oxidative Stress; dipeptidy; lidé; Dipeptides; sulfhydrylové sloučeniny; studie případů a kontrol; Treatment Outcome; Myelodysplastic Syndromes; oxidace-redukce; myelodysplastické syndromy; Case-Control Studies; Oxidation-Reduction; Iron; Malondialdehyde; Sulfhydryl Compounds; malondialdehyd; dusičnany; přetížení železem; Nitrites; ferritiny; Humans